The Rāmāyaṇa of Vālmīki: the complete English translation - Vālmīki (Princeton library of Asian translations, 2021)
Part I. Introduction: 1. Introduction -- 2. About the Translation -- Part II. The Rāmāyaṇa of Vālmīki: 3. The Bālakāṇḍa -- 4. The Ayodhyākāṇḍa -- 5. The Araṇyakāṇḍa -- 6. The Kiṣkindhākāṇḍa -- 7. The Sundarakāṇḍa -- 8. The Yuddhakāṇḍa -- 9. The Uttarakāṇḍa -- Glossary of Important Sanskrit Words, Proper Nouns, and Epithets -- Glossary of Weapons -- Bibliography -- Index.